1995
DOI: 10.1111/j.1365-2125.1995.tb04554.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender related changes in stereoselective pharmacokinetics and pharmacodynamics of verapamil and norverapamil.

Abstract: 1 Pharmacokinetics and pharmacodynamics of R-and S-verapamil and R-and Snorverapamil were studied at steady state following administration of 180 mg verapamil delivered by a controlled-release gastrointestinal therapeutic system (COER-verapamil). 2 Of the 30 young (19 to 43 years) and 30 elderly subjects (65 to 80 years) enrolled, approximately half of each age group were women; all subjects were healthy and none were smokers.3 Mean R-and S-verapamil and R-and S-norverapamil Cmax, Cmin, and AUC values for elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 13 publications
(30 reference statements)
1
22
2
Order By: Relevance
“…Weight-normalized verapamil clearance (CYP3A4 metabolized but also Pgp substrate/inhibitor) is as much as 50% greater in older women than in older men [ 28 ]. Another interesting example is the case of β -blockers.…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Weight-normalized verapamil clearance (CYP3A4 metabolized but also Pgp substrate/inhibitor) is as much as 50% greater in older women than in older men [ 28 ]. Another interesting example is the case of β -blockers.…”
Section: Pharmacologymentioning
confidence: 99%
“…However, another study that examined sex-based pharmacokinetic differences for oral verapamil showed that the reduction in mean arterial blood pressure owing to the drug was closely correlated with its plasma concentration, although without any interaction by sex [ 28 ]. Women had a higher response rate and a major decrease in blood pressure with amlodipine, compared with men [ 45 ].…”
Section: Calcium Antagonistsmentioning
confidence: 99%
“…It lowers SBP and DBP and is capable of achieving target BPs in a majority of patients when given as monotherapy. Its high efficacy in treating BP in older patients may be at least partly due to differences in the pharmacokinetics of the drug among age groups, in particular higher maximum concentrations and slower clearance from the plasma in elderly patients 23 ; however, these changes do not appear to increase the risk of adverse events. The CODAS-verapamil formulation may be especially beneficial in elderly patients with hypertension because it delivers peak concentrations of verapamil between 6 a.m. and noon to coincide with morning BP surge, a period during which there is an increased incidence of cardiovascular and stroke events in these vulnerable people.…”
Section: Resultsmentioning
confidence: 99%
“…Verapamil is a calcium ion influx inhibitor, having antiarrhythmic, antianginal and antihypertensive properties [4]. Verapamil undergoes extensive first-pass metabolism and is both a cytochrome P450 and P-glycoprotein substrate [3], so it is expected that the pharmacokinetic parameters may be different between the two genders.…”
Section: Introductionmentioning
confidence: 99%